Rejoinder to Rosser, O'Donnell, and Carrión Álvarez and Ehnts on their criticisms of my ergodic/nonergodic formulation of Keynes's concept of an actuarial certain future vs. an uncertain future. Issue 3 (2nd July 2016) - Davidson, Paul
ABSTRACT: This article provides my responses to recent criticisms of my argument associating Keynes's concept of uncertainty with Keynes's explicit statement that in our world of experience applying the "probability calculus" to historic data does not produce actuarial certain knowledge of future economic outcomes. Furthermore I have tried to explain, using Keynes' own written statements how Keynes's General Theory differs from old classical theory, new classical theory, Samuelson's Keynesian Theory, and New Keynesian Theory.